Monitoring Major Sugars in Greek Commercial Fir Honey and their Role in Geographical Differentiation, using Chemometrics (Global Journal of Medical Research, 2017)
Abstract not found
Keywords: commercial fir honey; sugars; high pressure liquid chromatography; refractive index; differentiation